ANALISIS OCR, PD, DAN TP TERHADAP IMPULSE BUYING PADA LIVE STREAMING SHOPEE - Putri, Ellysya Tallita; Muslih, Basthoumi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
The purpose of this study is to analyze the influence of Online Customer Review (OCR), Price Discount (PD), and Time Pressure (TP) on impulse buying during Shopee live streaming. A quantitative approach was employed using multiple linear regression analysis. The population in this study consisted of 337 active students from the 2021 cohort of the Management Study Program at Universitas Nusantara PGRI Kediri. A total of 183 respondents were selected using the Slovin formula with a 5% margin of error and a nonprobability sampling technique through simple random sampling, based on the criteria of being active Shopee users. The results show that OCR, PD, and TP have a positive and significant effect on impulse buying, both partially and simultaneously. These findings indicate that the three factors are key drivers of impulsive purchasing behavior during live streaming sessions. The novelty of this study lies in its focus on the impulse buying behavior of university students on the Shopee Live platform, which remains underexplored in the context of e-commerce in Indonesia.